Pengembangan Modul Matematika Berbasis Problem Solving pada Materi Vektor - Ariskasari, Dewi; Pratiwi, Dona Dinda (Universitas Islam Negeri Raden Intan Lampung, 2019)
This study aims to develop, determine the response and effectiveness of problem-based mathematical modules on vector material. This type of research is research and development or better known as Research and Development (R&D). The approach model used in this study is ADDIE. Data analysis techniques in this study were used to calculate the validity of the validators, the response of educators and students, and the effectiveness of mathematics teaching materials. The results of the validation test conducted by the validator are 3.24 the criteria are quite valid. The results of educator responses 3.21 with interesting criteria, response to small-scale trials of 3.4 with very interesting responses and field trials of 3.8 with very interesting responses. The results of the effectiveness test conducted during the field test got a percentage of 61% with effective criteria. From these data it shows that instructional materials are feasible to use based on the educator's response and effectiveness carried out by students, so the development of mathematical modules is appropriate for use in schools.